Medium-term Outcomes of Unsutured Scleral Flap Trabeculectomies. Issue 8 (August 2016) - Wang, Bob Z.; Ang, Ghee Soon; Meagher, Peter
Abstract : Purpose: To examine the clinical characteristics and medium-term outcomes of unsutured scleral flap trabeculectomies. Patient and Methods: A retrospective review of 45 patients who underwent 50 unsutured scleral flap trabeculectomies by a single ophthalmic surgeon. Information pertaining to each patient's demographic details, preoperative assessment, surgical procedure, and 2 years of postoperative management were obtained. Results: The average age of patients was 72.4±12.5 (range, 30 to 97) years. The diagnosis was primary open-angle glaucoma in 38 (76.0%) cases. The average preoperative, 1 year postoperative and 2-year postoperative intraocular pressure (with number of topical antiglaucoma medications) were 20.8 (2.5), 13.2 (0.4), and 12.6 mm Hg (0.7), respectively. The procedure performed was a trabeculectomy alone in 32 (64.0%) cases, and combined trabeculectomy and phacoemulsification in 18 (36.0%) cases. Four were performed with mitomycin C. Three procedures (6%) had intraoperative complications (2 iris prolapses, 1 subconjunctival hemorrhage). Seven procedures were complicated by a postoperative choroidal detachment, which were managed conservatively and resolved spontaneously over time. There was 1 case (2%) of postoperative hypotony, which failed to resolve (intraocular pressure of <6 mm Hg for >3 months). Conclusions: The majority of unsutured scleral flap trabeculectomies had an acceptable risk profile and resulted in a decrease in the intraocular pressure at 2 years postoperatively. Abstract : Supplemental Digital Content is available in the text.